(untitled) (Research, Society and Development, 2021)
Ostomy or stoma represents the opening made in a surgical procedure for the exteriorization of the intestine through the abdominal cavity. The impact of changes resulting from stomas directly affects self-image, which can cause feelings of sadness, repulsion and insecurity in face of the feeling of mutilation and inability to lead a normal life. In this sense, this article is an integrative literature review and aims to verify the applicability of Orem’s Theory to ostomy patients in studies already carried out. Ostomized patients present a change in quality of life, since the surgical procedure triggers changes in self-esteem, mental health and routine of these individuals. From this perspective, Orem’s Theory presents itself as a tool capable of identifying the individual’s health deviations, establishing interventions based on the Theories of Nursing Systems and promoting effective self-care. Finally, ostomies compromise not only the biological dimensions, physiological patterns and self-image, but also the individual’s psychosocial relationships. In this context, Orem’s Nursing Theory is fundamental for ostomy patients, as it encompasses holistic care by signaling health deviations and classifying the nursing system adopted in each case.